Pendekatan Keterampilan Proses dalam Pembelajaran Ilmu Pengetahuan Alam (IPA) bagi Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar (PGSD) - Pratiwi, Indah; Sitanggang, Raysyah Putri (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
Teaching is a dynamic and creative process, requiring educators to plan and deliver instruction that not only avoids monotony but also actively engages students in learning. In the context of science education for prospective elementary school teachers, varied instructional approaches—particularly the process skills approach—are essential. This study aims to examine the ability of Primary School Teacher Education (PGSD) students to implement the process skills approach during classroom teaching simulations in science subjects. Employing a descriptive qualitative method, data were obtained through assessments of students’ lesson plans and their simulation performances. The subject matter focused on energy topics for fourth-grade elementary students. The findings reveal that 70% of the lesson plans met the 'good' criteria and 30% were rated 'sufficient', with an average score of 80.40. In terms of simulation performance, 39% of students demonstrated an 'excellent' application of the process skills approach, 31% were categorized as 'good', 23% as 'sufficient', and 8% as 'poor', yielding an overall average score of 80.71. These results indicate a generally strong ability among PGSD students to design and simulate science instruction using the process skills approach, though a small proportion still requires significant improvement.